Logo Redesign DB Transport.Id - Fauzan Nurzaman; Rachmawati, Ine; Awalaturrohmah, Yuni (Sean Institute, 2025)
The tourism industry needs a travel agency to provide convenience for tourists, good beginner and old customers, and manage needs like transportation, tickets, and accommodation. One of the providers of services is the established DB Transport. ID since 2018 and initially focused on rental cars, then developed to tour and travel services in 2023, providing various package travel and facilities to support comfortable customers. However, the old DB Transport.id logo was considered not yet to reflect a professional company's vision, mission, and characteristics, because it was monotonous and lacked visual elements of its philosophy. Therefore, the design reuses Alina Wheeler's (2013) brand identity method to strengthen visual identity, enhance brand sales, and build a more professional and competitive image in the transportation and tourism industry, especially in the Cirebon area and its surroundings.